Patulous upper esophageal sphincter - an unusual endoscopic finding - James, Allwin; Karunakaran, Premkumar; Kini, Ratnakar; Thangavel, Pugazhendhi (Turkish Journal of Gastroenterology, 2018)
Abstract The upper esophageal sphincter (UES) has various important functions, such as protection of the airway from aspiration and conduct of bolus into esophagus, which are controlled by complex neuronal mechanisms. The functions will be affected when there is malfunction of the UES due to various etiologies. Here we present an 80-year-old male with non-progressive dysphagia and patulous UES incidentally found on esophagoduodenoscopy. There are no documented cases of idiopathic patulous UES in literature. Endoscopists must be aware of this rare condition while evaluating a patient presenting with oropharyngeal dysphagia. Cite this article as: James A, Karunakaran P, Kini R, Thangavel P. Patulous upper esophageal sphincter - an unusual endoscopic finding. Turk J Gastroenterol 2018; 29: 112-4.